Dimensional Accuracy Achievable in Wire-cut Electrical Discharge Machining - Islam, Mohammad Nazrul; Rafai, Noor; Subramanian, S. (Spinger, 2011)
Wire-cut electrical discharge machining (WEDM) is a popular choice for machining hard and difficult to machine materials with very close tolerances. However, this widely held assumption of high accuracy of WEDM needs to be investigated which is the primary aim of this project. This paper presents experimental and analytical results of an investigation into dimensional accuracy achievable in WEDM. Three techniques viz. traditional analysis, Taguchi method and Pareto ANOVA analysis are employed to determine the effects of six major controllable machining parameters, viz. discharge current, pulse duration, pulse gap frequency, wire speed, wire tension and dielectric flow rate on three key dimensional accuracy characteristics of prismatic component parts viz. linear dimensional error, flatness error and perpendicularity error of corner surfaces. Subsequently, the input parameters are optimized for maximizing the dimensional accuracy characteristics. The results indicate that the dimensional accuracy achievable in wire-cut electrical discharge machining is not as high as it is anticipated.